An Exploration of Determinants of Anemia in Pregnant Women at Buakayu Community Health Center Tana Toraja Regency - Erni Yetti R; Zadrak Tombeg; Anto J. Hadi; Sumardi Sudarman; Syamsopyan Ishak; Fitri Rahma Handayani (Journal of Public Health and Pharmacy, 2024)
Introduction: Anemia on pregnant women is a global health problem that has serious impacts on the mother and fetus. The objective of the study was to explore the determinants of anemia on pregnant women at Buakayu Community Health Center, Tana Toraja Regency. Methods: The study used an observational study with a cross-sectional design. The sample was pregnant women who visited the Buakayu Community Health Center for antenatal examination using an accidental sampling technique for 11 days. The data was collected through structured interviews and laboratory examinations. Data analysis was carried out using descriptive statistical methods (univariate), bivariate, and regression analysis to determine the variables most related to independent variables and anemia in pregnant women. Results: The results of the study showed that diet (p=0.001), dietary restrictions (p=0.005), consumption of Fe tablets (p=0.000), and provision of additional food (p=0.000) were related to anemia incidence on pregnant women. Conclusion: It can be concluded that diet, dietary restrictions, consumption of Fe tablets, and provision of additional food are factors that contribute to anemia incidence on pregnant women at the Buakayu Community Health Center area. It is hoped that the implications of the study can be used as a basis for designing appropriate interventions in dealing with anemia on pregnant women at the Health Center level.